KEPATUHAN MEMBAYAR ZAKAT: ANALISIS KUTIPAN DAN KETIRISAN ZAKAT FITRAH DI SELANGOR: Compliance of Zakah Payment: Analysis of Zakat Fitrah Collection and Leakage in Selangor - Mohd Hussin, Mohd Yahya; Muhammad, Fidlizan; Ahmad, Mohamad Ali Roshidi (Jurnal Syariah, 2019)
This study aims to identify and analyse the number of collections of zakah fitrah in Selangor through the formal payment channel. By using the data on the amount of zakah fitrah collection, the number of Muslims and zakah fitrah collection rate in Selangor from 1995 to 2011, the research findings show that the amount of collection is increasing from year to year except for 1998. However, the number of payers who do not use the formal channel is also high. In addition, the amount of zakah fitrah leakage without going through formal institutions also demonstrates a large increase from RM1.8 million in 1995 to RM5.2 million in 2011. This result shows that the zakah institution is in need of continuous improvement involving the administration, management, and collection and distribution system.